2023
DOI: 10.1097/md.0000000000031465
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary infection of Schizophyllum commune diagnosed by metagenomic next- generation sequencing: A case report

Abstract: Rationale: Fungal infection is common and difficult to be diagnosed timely in clinical, for its various kinds and similar manifestations. The rare pulmonary fungal infection such as Schizophyllum commune was one of the harder ones and misdiagnosed in usual. Patient concerns: We report a 32-year-old female which was diagnosed with Metagenomic Next-Generation Sequencing (mNGS). She was hospitalized with the complaint of 4 months and more of repeated cough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…This case study suggests that S. commune may cause granulomatous nasopharyngitis and surgical resection of the nodules, and subsequent medication with antifungal agents is the curative therapy for a captive cheetah. In this case, treatment with fluconazole was insufficient; in contrast, itraconazole exhibited a curative therapeutic effect, as suggested in previous studies [ 7 , 12 , 13 ]. However, the therapeutic effects of surgical treatment combined with antifungal medication remain unclear, and the relatively long-term remission of 73 days after fluconazole administration might have been due to the debulking of gross lesions.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…This case study suggests that S. commune may cause granulomatous nasopharyngitis and surgical resection of the nodules, and subsequent medication with antifungal agents is the curative therapy for a captive cheetah. In this case, treatment with fluconazole was insufficient; in contrast, itraconazole exhibited a curative therapeutic effect, as suggested in previous studies [ 7 , 12 , 13 ]. However, the therapeutic effects of surgical treatment combined with antifungal medication remain unclear, and the relatively long-term remission of 73 days after fluconazole administration might have been due to the debulking of gross lesions.…”
supporting
confidence: 63%
“…The basidiomycete Schizophyllum commune is a common mushroom species that is isolated from various natural sources. However, it has been reported that the mushroom is occasionally responsible for infections in humans and animals [ 1 , 4 , 6 , 7 , 11 , 13 ]. In humans, S. commune infection has been reported as allergic bronchopulmonary mycosis, allergic fungal rhinosinusitis, and mucoid impaction of the bronchi [ 3 , 5 , 6 , 10 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In European and American countries, it is considered inedible, largely due to cultural tastes, small stature, and its presumed leathery texture. Literature reports on S. commune have mainly implicated the fungus with multiple pulmonary manifestations ranging from sinusitis, allergic bronchopulmonary mycoses, asthma, chronic eosinophilic pneumonia, and so on [ 251 , 252 ].…”
Section: Resultsmentioning
confidence: 99%